Acta Crystallographica Section C: Structural Chemistry - Acta Crystallographica Section C: Structural Chemistry (Wiley, 2026)
Acta Crystallographica Section C, Structural Chemistry is the premier venue for publishing studies where structural insights drive breakthroughs across the chemical sciences, highlighting interesting research facilitated by the determination, calculation or analysis of structures. Articles published in the journal may report results relevant to structural chemistry obtained through crystallographic techniques such as electron, powder and X-ray diffraction, as well as other complementary techniques including, but not limited to, spectroscopic and computational studies. Articles may report important new structural information on any type of chemical species, including polymorphs, coordination polymers, inorganics and minerals, liquid crystals, nanostructures, pharmaceutical compounds and natural products. Additionally, data-driven discovery studies that mine crystallographic and spectroscopic databases to uncover novel structure-property correlations and predictive models are featured.
FI 0.24
Q4
Keywords: Earth; Space & Environmental Sciences; Crystallography; Cristalografía; Acuerdos transformativos; Transformative agreements; Espectroscopía; Difracción electrónica